Surface-based and solid shell formulations of the 7-parameter shell model for layered CFRP and functionally graded power-based composite structures - Reinoso; Paggi; Areias, P; Blasquez (My University, 2018)
In this study, we present the extension of the so-called 7-parameter shell formulation to layered CFRP and functionally graded power-based composite structures using two different parametrizations: (i) the three- dimensional shell formulation, and (ii) the solid shell approach. Both numerical strategies incorporate the use of the Enhanced Assumed Strain (EAS) and the Assumed Natural Strain (ANS) methods to alleviate lock- ing pathologies and are implemented into the FE code ABAQUS. The applicability of the current develop- ments is demonstrated by means of several benchmark examples, whose results are compared with refer- ence solutions using shell elements of ABAQUS, exhibiting an excellent level of accuracy